Ethics in aesthetics: social media. (2nd September 2019) - Kisyova, Rumi; Rahman, Shakeel M; Dheansa, Baljit; Karkhi, Alex
Abstract : Over the last few decades, aesthetic procedures and plastic surgery have been associated with delaying the ageing process. However, the rise of social media, alongside the 'Kardashian effect', has brought about a new phenomenen in younger generations seeking to enhance their beauty